Can exercise therapy combined with transcranial direct current stimulation further improve balance ability in individuals with chronic ankle instability? A systematic review and meta-analysis - Zheng, Jiawei; Chen, Ruixiong; Wang, Sifan; Chen, Jian; Lin, Xikai (Frontiers in Physiology, 2025)
ObjectivesTo evaluate whether transcranial direct current stimulation (tDCS) combined with exercise therapy enhances balance ability in chronic ankle instability (CAI) individuals.MethodsSystematic searches were conducted in PubMed, Embase, Web of Science, Cochrane Library, and Scopus databases up to July 10, 2025. The Cochrane Risk of Bias tool version 2. Was used to assess the methodological quality of studies meeting the inclusion criteria. Meta-analyses were performed using random-effects models, with results expressed as standardized mean differences (SMD) and 95% confidence intervals (95% CI). Evidence quality was evaluated using the GRADE methodology.ResultsEight studies involving 216 participants were included in the meta-analysis. Overall analysis revealed that tDCS combined with exercise therapy did not significantly improve dynamic balance (SMD: 0.08, 95% CI: −0.36 to 0.52, P = 0.72) or static balance (SMD: −0.53, 95% CI: −1.08 to 0.02, P = 0.06) in individuals with CAI. Subgroup analysis by exercise type showed that tDCS combined with non-balance training significantly enhanced dynamic balance ability (SMD: 0.52, 95% CI: 0.07 to 0.97, P = 0.02), while tDCS combined with balance training showed no significant improvements in either composite dynamic balance measures (SMD: −0.26, 95% CI: −0.82 to 0.30, P = 0.36) or Y-balance reach distances in any direction (P > 0.05 for all directions).ConclusiontDCS provides therapeutic benefits for dynamic balance only when combined with non-balance exercises. Current evidence is insufficient to demonstrate improvements in static balance with tDCS adjunctive therapy.